2012
DOI: 10.1038/ncomms1735
|View full text |Cite
|
Sign up to set email alerts
|

Lipid storage disorders block lysosomal trafficking by inhibiting a TRP channel and lysosomal calcium release

Abstract: Lysosomal lipid accumulation, defects in membrane trafficking, and altered Ca2+ homeostasis are common features in many lysosomal storage diseases. Mucolipin TRP channel 1 (TRPML1) is the principle Ca2+ channel in the lysosome. Here we show that TRPML1-mediated lysosomal Ca2+ release, measured using a genetically-encoded Ca2+ indicator (GCaMP3) attached directly to TRPML1 and elicited by a potent membrane-permeable synthetic agonist, is dramatically reduced in Niemann-Pick (NP) disease cells. Sphingomyelins (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
583
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 427 publications
(649 citation statements)
references
References 39 publications
40
583
2
2
Order By: Relevance
“…5f). Filipin [39][40][41][42] stainings further confirmed a strong accumulation of cholesterol in TPC2 À / À hepatocytes after CD treatment (Fig. 6a).…”
Section: Articlesupporting
confidence: 54%
“…5f). Filipin [39][40][41][42] stainings further confirmed a strong accumulation of cholesterol in TPC2 À / À hepatocytes after CD treatment (Fig. 6a).…”
Section: Articlesupporting
confidence: 54%
“…In human, loss-of-function mutations in TRPML1 are the direct cause of Mucolipidosis type IV (MLIV), an autosomal recessive lysosomal storage disease characterized by abnormal neurodevelopment, retinal degeneration and iron-deficiency anemia 3-6 . Due to its direct linkage to MLIV disease, TRPML1 has been a potential target for small molecule therapeutics and several synthetic small molecule agonists have been developed 12,20 .…”
Section: Main Textmentioning
confidence: 99%
“…response to trafficking cues, such as changes in levels of PI(3,5)P 2 , a lysosome-localized phosphoinositide (7,15,(18)(19)(20)(21). ML1-mediated lysosomal Ca 2+ release may regulate many aspects of lysosomal trafficking, including lysosome to trans-Golgi-network (TGN) retrograde trafficking, autophagosome-lysosome fusion, lysosome reformation, and lysosomal exocytosis (15,19,22,23).…”
Section: Significancementioning
confidence: 99%
“…ML1-mediated lysosomal Ca 2+ release may regulate many aspects of lysosomal trafficking, including lysosome to trans-Golgi-network (TGN) retrograde trafficking, autophagosome-lysosome fusion, lysosome reformation, and lysosomal exocytosis (15,19,22,23). Moreover, it has been demonstrated that nutrient starvation affects phosphoinositide dynamics and Ca 2+ signaling (16,18,24).…”
Section: Significancementioning
confidence: 99%